EPIDEMIOLOGI DIGITAL DAN DETERMINAN SOSIAL PADA LAYANAN PRIMER: TINJAUAN LITERATUR DAMPAK KOMPETENSI NAKES DAN SISTEM INFORMASI TERHADAP KETERLIBATAN PASIEN MELALUI MEDIASI PENGALAMAN PASIEN DI PUSKESMAS KABUPATEN LOMBOK TENGAH NTB - Darma Karno; Yuly Peristiowati (Journal of Innovation Research and Knowledge, 2026)
Background: Digital health transformation in primary care requires the integration of technology and human resource competence. In Central Lombok Regency, the effectiveness of digital epidemiology is heavily influenced by social determinants and the capacity of health workers to manage information systems. Objective: This study aims to analyze the impact of health worker competence and information system quality on patient engagement, positioning patient experience as a mediating variable through a systematic literature review. Methods: This research employs the Systematic Literature Review (SLR) method. Literature searches were conducted on Scopus and Google Scholar databases within the 2014-2024 timeframe. Inclusion criteria focused on studies discussing primary health information systems, health workers' digital competence, and patient behavior. Results: Synthesis of selected literature indicates that health workers' digital competence and information system quality significantly enhance the quality of interaction in community health centers (Puskesmas). Patient experience is proven to be a crucial mediating variable; efficient digital services create positive perceptions that encourage patients to become more actively involved in their health management. However, social determinants such as community digital literacy remain a challenge in optimizing patient engagement. Conclusion: Strengthening health worker competence and information system reliability are key prerequisites for creating a superior patient experience, which ultimately increases active community participation in the digital epidemiology ecosystem at primary care levels.